The Influence Of Parents' Authoritary Parenting Styles On Students' Psychological Well-Being In An Academic Environment - Hani Magdalena Panjaitan; Karina M. Brahmana (CV Putra Publisher, 2025)
This study aims to determine the Influence of Authoritarian Parenting Patterns of Parents on the Psychological Well-being of Students in an Academic Environment at HKBP Nommensen University Medan. Based on the results of research on the influence of authoritarian parenting patterns on psychological well-being in students of HKBP Nommensen University Medan, it can be concluded as follows. Based on the results of descriptive analysis, the average (mean) score of authoritarian parenting patterns was 18.95 with a standard deviation of 5.236, while the average psychological well-being score was 22.34 with a standard deviation of 5.397. These results indicate that respondents have a level of authoritarian parenting patterns and psychological well-being that is in the moderate category. Based on the results of the classical assumption test, the research data meets the requirements for simple linear regression analysis. The results of the normality test show a significance value of 0.200 (> 0.05) so that the data is normally distributed. The results of the linearity test show a Deviation from Linearity value of 0.475 (>0.05) which means the relationship between the authoritarian parenting variable and psychological well-being is linear. Furthermore, the results of the heteroscedasticity test show a significance value of 0.108 (>0.05) so that there are no symptoms of heteroscedasticity in the regression model. The results of the simple linear regression test show that authoritarian parenting has a significant effect on the psychological well-being of students at HKBP Nommensen University Medan, with a significance value of 0.000 (<0.05). The regression coefficient value of 0.449 indicates a positive influence between authoritarian parenting on psychological well-being in research respondents. The R Square value of 0.190 indicates that authoritarian parenting contributes 19% to the variation in students' psychological well-being, while 81% is influenced by other factors not examined in this